Block of Voltage-Gated Sodium Channels as a Potential Novel Anti-cancer Mechanism of TIC10 - Fuchs, Eva; Messerer, David Alexander Christian; Karpel-Massler, Georg; Fauler, Michael; Zimmer, Thomas; Jungwirth, Bettina; Föhr, Karl Josef (Frontiers in Pharmacology, 2021)
Background: Tumor therapeutics are aimed to affect tumor cells selectively while sparing healthy ones. For this purpose, a huge variety of different drugs are in use. Recently, also blockers of voltage-gated sodium channels (VGSCs) have been recognized to possess potentially beneficial effects in tumor therapy. As these channels are a frequent target of numerous drugs, we hypothesized that currently used tumor therapeutics might have the potential to block VGSCs in addition to their classical anticancer activity. In the present work, we have analyzed the imipridone TIC10, which belongs to a novel class of anti-cancer compounds, for its potency to interact with VGSCs. Methods: Electrophysiological experiments were performed by means of the patch-clamp technique using heterologously expressed human heart muscle sodium channels (hNav1.5) which are among the most common subtypes of VCSCs occurring in tumor cells. Results: TIC10 angular inhibited the hNav1.5 channel in a state- but not use-dependent manner. The affinity for the resting state was weak with an extrapolated Kr of about 600 µM. TIC10 most probably did not interact with fast inactivation. In protocols for slow inactivation, a half maximal inhibition occurred at around 2 µM. This observation was confirmed by kinetic studies indicating that the interaction occurred with a slow time constant. Furthermore, TIC10 also interacted with the open channel with an affinity of approximately 4 µM. The binding site for local anesthetics or a closely related site is suggested as a possible target as the affinity for the well-characterized F1760K mutant was reduced more than 20-fold compared to wildtype. Among the analyzed derivatives ONC212 was similarly effective as TIC10 angular while TIC10 linear more selectively interacted with the different states. Conclusion: The inhibition of VGSCs at low micromolar concentrations might add to the antitumor properties of TIC10.